2019
DOI: 10.1017/s1368980019001368
|View full text |Cite
|
Sign up to set email alerts
|

Project Spraoi: a two-year longitudinal study on the effectiveness of a school-based nutrition and physical activity intervention on dietary intake, nutritional knowledge and markers of health of Irish schoolchildren

Abstract: Objective:To assess the effectiveness of a nutrition and physical activity (PA) intervention on dietary intake (DI), nutritional knowledge (NK), blood pressure (BP), anthropometric measures and cardiorespiratory fitness (CRF) of schoolchildren.Design:Longitudinal study. DI, NK, BMI, waist-to-height ratio (WHtR), BP and CRF were all measured/calculated prior to (October 2014) and at the end of (June 2016) intervention delivery.Setting:Two primary schools (one intervention and one control), Cork, Ireland.Partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…Among the successful diet and physical activity interventions, three involved teachers' training and participation of children's parents [31][32][33][34], one involved teachers' training [35] and one involved participation of children's parents [36]. Teachers' training was conducted through workshops concerning healthy habits for school children and/or through teaching materials (re-printed posters for drinking rules or pre-prints to record children's fluid intake).…”
Section: Diet and Physical Activity Interventionsmentioning
confidence: 99%
See 4 more Smart Citations
“…Among the successful diet and physical activity interventions, three involved teachers' training and participation of children's parents [31][32][33][34], one involved teachers' training [35] and one involved participation of children's parents [36]. Teachers' training was conducted through workshops concerning healthy habits for school children and/or through teaching materials (re-printed posters for drinking rules or pre-prints to record children's fluid intake).…”
Section: Diet and Physical Activity Interventionsmentioning
confidence: 99%
“…Three studies had a benefit on anthropometric measurements [31][32][33]36]. Specifically, one study showed a reduction in the incidence of obesity [31,32], another one showed an increase in the % of children of healthy body weight [33], and one found a reduction in the waistto-height ratio, but this reduction was recorded only in 10-year-old children [36]. Furthermore, two studies had a beneficial effect on biomarkers and blood pressure (BP) [33,36].…”
Section: Diet and Physical Activity Interventionsmentioning
confidence: 99%
See 3 more Smart Citations